Outside Insiders: Understanding the Role of Contracting in the Careers of Managerial Workers - Anderson, Tracy; Bidwell, Matthew (Organization Science, 2019)
We explore the role that contracting plays within the careers of managerial workers. Contracting distances workers from organizational coordination and politics, aspects of organizational life that are often central to the managerial role. Nonetheless, managerial workers make up a substantial proportion of the contracting workforce. Qualitative interviews with managerial contractors indicate that the tension between the natures of contracting and managerial work means that managerial contractors carry out substantially more bounded work than regular employees, and that this boundedness can shape the role that contracting plays in their careers. Examining the employment histories of MBA alumni of a U.S. business school, we show that workers with fewer subordinates and greater personal demands are more likely to enter contracting. We also find that contractors report better work–life balance but receive lower pay both while contracting and in subsequent regular employment. Whereas prior research has highlighted the financial benefits and temporal demands of contracting for highly skilled workers, our findings introduce important boundary conditions to our understanding of high-skill contracting: the nature of the occupation is critical.